Obtenção de polímeros de LCC para aplicação como antioxidante de biodiesel de soja - Figueiredo, Francisco Cardoso (2009)
Biodiesel is a fuel obtained from vegetable oils, such as soy, castorbean, among others. The monoester of fatty acid of these oils have chains with mono, di and tri double connections. The presence of these insaturations are susceptible to oxidization. Antioxidants are substances able to prevent oxidization from oils, fats, fat foods, as well as esters of Alquila( biodiesel). The objective of this work is to summarize a new antioxidant from the Cashew Nut Shell Liquid (CNSL) using the electrolysis technique. A current of 2 amperes was used in a single cell of only one group and two eletrodos of stainless steel 304 in a solution of methanol, together with the eletrolits: acetic acid, sodium chloride and sodium hydroxide, for two hours of agitation. The electrolysis products are characterized by the techniques of cromatography in a thin layer, spectroscopy of infrared and gravimetric analysis. The material was submitted to tests of oxidative stability made by the techniques of spectropy of impendancy and Rancimat (EN 14112). The analyses of characterization suggest that the polimerization of the electrolytic material ocurred. The application results of these materials as antioxidants of soy biodiesel showed that the order of the oxidative stability was obtained by both techniques used